2014
DOI: 10.1016/j.biomaterials.2014.04.038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyperbranched polyglycerol coatings on drug delivery using degradable polymer nanoparticles

Abstract: A key attribute for nanoparticles (NPs) that are used in medicine is the ability to avoid rapid uptake by phagocytic cells in the liver and other tissues. Poly(ethylene glycol) (PEG) coatings has been the gold standard in this regard for several decades. Here, we examined hyperbranched polyglycerols (HPG) as an alternate coating on NPs. In earlier work, HPG was modified with amines and subsequently conjugated to poly(lactic acid) (PLA), but that approach compromised the ability of HPG to resist non-specific ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 31 publications
4
110
0
1
Order By: Relevance
“…We achieved a loading of CPT in our nanoparticles of $10% by weight; this value is higher than our theoretical loading of 8%, indicating that more PLGA was lost than CPT during the nanoparticle fabrication process. Loss of PLGA during nanoparticle fabrication has been reported previously (Sawyer et al, 2011), and our loading is consistent with the 5-25% loading reported by other groups encapsulating CPT in PLGA (Deng et al, 2014;McCarron et al, 2008). The average hydrated nanoparticle diameter measured by DLS ($200 nm) was larger than the diameter measured by SEM ($120 nm), which is expected, given that NPs will become hydrated in the aqueous environment required for DLS and that a fraction of nanoparticles will experience aggregation after resuspension.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We achieved a loading of CPT in our nanoparticles of $10% by weight; this value is higher than our theoretical loading of 8%, indicating that more PLGA was lost than CPT during the nanoparticle fabrication process. Loss of PLGA during nanoparticle fabrication has been reported previously (Sawyer et al, 2011), and our loading is consistent with the 5-25% loading reported by other groups encapsulating CPT in PLGA (Deng et al, 2014;McCarron et al, 2008). The average hydrated nanoparticle diameter measured by DLS ($200 nm) was larger than the diameter measured by SEM ($120 nm), which is expected, given that NPs will become hydrated in the aqueous environment required for DLS and that a fraction of nanoparticles will experience aggregation after resuspension.…”
Section: Discussionsupporting
confidence: 92%
“…The method for measuring release of CPT from nanoparticles was adapted from a method described previously (Deng et al, 2014). Nanoparticles (150 mg) with or without CPT were suspended in 2 ml of 1Â PBS and incubated at 37 C on a shaker.…”
Section: Controlled Releasementioning
confidence: 99%
“…PLA is one of the eco-friendly bioplastics with excellent biodegradability, processibility, less energy dependence and lower cost, which has been widely utilized in biomedical fields such as sutures, resorbable plates and screws, and drug delivery device [12][13][14][15][16]. The Food and Drug Administration (FDA) has also approved PLA for direct contact with biological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…33 Polymerization of L-LA in the presence of PG and Sn(Oct) 2 Table 3 (nos. [1][2][3][4][5][6][7][8].…”
Section: Preparation Of Multi-arm Pla In Presence Of Oligoglycerolsmentioning
confidence: 99%
“…1,2 They exhibit different physical properties in comparison to their linear homologues, such as lower viscosity in dilute solutions and in the melt, 3 poor mechanical properties and less susceptibility to form crystalline phases. 4 The solubility of HBPs depends mostly on the nature of HBP end groups, degree of branching and solvent.…”
Section: Introductionmentioning
confidence: 99%